Ossifying Parotid Carcinoma ex Pleomorphic Adenoma - Suresh Mohan; Sidharth V. Puram; Bharat Yarlagadda; Vania Nosé; Daniel G. Deschler (Case Reports in Otolaryngology)
We present a unique case of an extensively ossified carcinoma ex pleomorphic adenoma (CXPA) in a 76-year-old man with a five-year history of a slowly growing parotid mass. Fine-needle aspiration of the mass was nondiagnostic. A computed tomography (CT) scan of the lesion revealed a well-circumscribed mass with peripheral calcification. Initial pathological analysis suggested a benign parotid mass, but rigorous decalcification revealed noninvasive CXPA. The patient underwent complete resection of the mass and remained disease-free nine months later. Extensive ossification of a seemingly benign parotid mass may mask areas of carcinoma that may progress if left untreated.